The Epistemic Goods of Higher Education - Kotzee, Ben (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2018)
In this paper, I investigate two clashing perspectives regarding the good of the university: a socio-economic and an epistemic perspective. I position current writing on the university in the philosophy of education as being largely socio-economic and contrast this view to an earlier tradition of writing about the university that I position as mostly epistemic. Following on from this discussion, I review the university’s role in the distribution of social and epistemic goods. I hold that the university directly controls only the latter, not the former and hold that whatever socio-economic roles the university plays in society, it must do so through the distribution of knowledge in society. Next, I explore what this means for the university’s socio-economic functioning: I hold that seeing the good that the university distributes as knowledge places limits on its socio-economic functioning. Lastly, I ask what the university can do to promote epistemic justice in how it conducts teaching and research. I hold that one of the most important things that the university can do in the name of epistemic justice is to educate others (especially employers) about the true worth of a university degree.